CO2 line-mixing database and software update and its tests in the 2.1 μm and 4.3 μm regions. (January 2015) - Lamouroux, J.; Régalia, L.; Thomas, X.; Vander Auwera, J.; Gamache, R.R.; Hartmann, J.-M.
Abstract: An update of the former version of the database and software for the calculation of CO2 –air absorption coefficients taking line-mixing into account [Lamouroux et al. J Quant Spectrosc Radiat Transf 2010;111:2321] is described. In this new edition, the data sets were constructed using parameters from the 2012 version of the HITRAN database and recent measurements of line-shape parameters. Among other improvements, speed-dependent profiles can now be used if line-mixing is treated within the first order approximation. This new package is tested using laboratory spectra measured in the 2.1 μm and 4.3 μm spectral regions for various pressures, temperatures and CO2 concentration conditions. Despite improvements at 4.3 μm at room temperature, the conclusions on the quality of this update are more ambiguous at low temperature and in the 2.1 μm region. Further tests using laboratory and atmospheric spectra are thus required for the evaluation of the performances of this updated package. Highlights: High resolution infrared spectroscopy. CO2 in air. Updated tools. Line mixing database and software.